Does the high school external examination grades and the type of high school attended impact the academic performance of freshmen university students? - Olumide Sunday Adesina; Lawarence O. Obokoh; Olajumoke Olayemi Salami (STEM Education)
There is a general conception that high school academic performance and the type of school a child attends would determine his/her academic success in the university. In this study, 135 freshmen engineering students were sampled at the Redeemer's University, Osun State, Nigeria. The study aimed to determine if the Unified Tertiary Matriculation Examination (UTME) and the type of school attended impact on academic performance of students in the first year at the university. The results showed that there is a significant relationship between UTME scores and the results of engineering freshmen; that is, students who attended private secondary schools performed somewhat better than students who went to public secondary schools. Also, statistical analyses showed that the type of secondary school attended has a significant relationship with UTME scores in favor of students who attended private secondary schools. This study recommends that the government of Nigeria should make public secondary school more appealing to students who cannot afford private secondary schools by putting measures in place to train and employ qualified teachers, and improve teaching and learning conditions. The study aligns with the Sustainable Development Goals (SDGs) 4, to ensure inclusive and equitable quality education for all and lifelong learning.